Effects of drying on the quality characteristics and release of umami substances of Flammulina velutipes. (February 2023) - Wang, Jipeng; Jiang, Songying; Miao, Song; Zhang, Longtao; Deng, Kaibo; Zheng, Baodong
Abstract: The aim of this research was to study the effects of drying methods on the flavor substances of Flammulina velutipes, a common commercial edible fungus. Scanning electron microscopy, high performance liquid chromatography, amino acid analysis, and electronic tongue analysis were used to evaluate the quality characteristics and the release pattern of umami components from F. velutipes under hot air drying (HAD), vacuum drying (VD), and vacuum freeze-drying (VFD). Additionally, taste activity value, equivalent umami concentration value, and principal component analysis were performed. The results indicate each of the drying methods exhibited respective advantages. F. velutipes under VFD had better micro-spatial structure and high rehydration capacity, followed by HAD. In VD treatment, dried F. velutipes had the highest levels of free amino acids and organic acids, especially the umami amino acids Glu and Asp were significantly retained and released. Compared with other methods, the content of umami 5′-nucleotides (5′-IMP, 5′-GMP) in F. velutipes was the highest under HAD and at 50°C had the highest level of equivalent umami concentration (EUC) value. The results showed that the mutual regulation of flavor substances in F. velutipes was related to the drying method, and HAD at 50°C was the optimal method to preserve flavor substances and quality characteristics in F. velutipes . The results can provide a method reference for the production of dried Flammulina velutipes with good flavor. Highlights: Flammulina velutipes had the highest EUG value at hot air 50°C. The contents of flavor-presenting substances varied with temperature. 5ˈ-Nucleotide formation inhibited the degradation of free amino acids. Vacuum freeze-dried F. velutipes had best quality characteristics.